The Phenomenon of Brain Rot from the Perspective of Sufi Exegesis: A Study of Haqāʾiq al-Tafsīr by al-Sulamī: Fenomena Brain Rot dalam Perspektif Tafsir Sufistik: Studi atas Haqāʾiq al-Tafsīr Karya Abū ʿAbd al-Raḥmān al-Sulamī. - Nurhamidah Nurhamidah; Muhammad Rifan; Norhidayat Norhidayat (Institut Agama Islam Negeri Kerinci, 2026)
This study aims to examine the phenomenon of brain rot through the perspective of Sufi exegesis by analyzing Haqāʾiq al-Tafsīr of Abū ʿAbd al-Raḥmān al-Sulamī. The phenomenon of brain rot has emerged as a contemporary issue associated with cognitive decline and diminished spiritual awareness resulting from excessive exposure to repetitive and low-quality digital content. This research employs a qualitative library research design using a Sufi hermeneutical approach. The primary source is Haqāʾiq al-Tafsīr, while secondary sources include Qur’anic commentaries, Sufi literature, and contemporary studies on brain rot, digital psychology, and neuroscience. The collected data were analyzed through content analysis and thematic analysis. The findings indicate that al-Sulamī conceptualizes spiritual decline as a condition of ghaflah (heedlessness), in which the heart is veiled by the dominance of the nafs and becomes detached from dhikr and deep reflection (tadabbur). In the context of the digital era, this condition corresponds to the characteristics of brain rot, where human attention is dominated by digital distraction and superficial information consumption. The study further identifies three Sufi-based approaches proposed in Haqāʾiq al-Tafsīr to restore spiritual awareness: muhāsabah al-nafs (self-accountability), continuous dhikr accompanied by khalwah (spiritual retreat), and the transformation of information consumption into reflective tadabbur. These findings demonstrate the relevance of al-Sulamī’s Sufi exegesis as a conceptual framework for understanding and responding to the spiritual dimensions of brain rot in contemporary digital society.